The influence of the geological–geomorphological setting on human settlements and historical urban development: the case study of Isernia (southern Italy). Issue 4 (28th July 2021) - Aucelli, Pietro P. C.; Valente, Ettore; Di Paola, Gianluigi; Amato, Vincenzo; Cesarano, Massimo; Cozzolino, Marilena; Pappone, Gerardo; Scorpio, Vittoria; Rosskopf, Carmen M.
ABSTRACT: The map is aimed at illustrating the relationships between landscape evolution and human occupation in the Isernia basin since the Middle Pleistocene. We carried out a detail scale geological–geomorphological investigation integrated with archaeological data. Overall data suggest enhanced landscape modification related to the long-term evolution of the Isernia basin. Moreover, during the Middle Pleistocene an alluvial plain environment was present, as testified also by the famous Lower Palaeolithic site of Isernia La Pineta dated to ca. 600 ky. From 600 ky onwards, extensional tectonics and related valley incision reshaped the Isernia basin, with the formation of terraced surfaces and the deposition of a travertine plateau. Archaeological findings from the Lower Palaeolithic up to the Chalcolithic Age testify to pre- and protohistoric settlements on these surfaces. In historical times, Romans settled on the Isernia terrace ridge taking advantage of the outcropping travertines to support wall foundations and to extract construction material.